THE EFFECT OF COMPANY SIZE, FUNDING DECISIONS, AND FINANCIAL PERFORMANCE ON FIRM VALUE - Juli Ismanto (Kunuz: Journal of Islamic Banking and Finance, 2023)
This study aims to determine the effect of company size, funding decisions, and financial performance on firm value. Secondary data is sourced from the financial statements of companies in the Industrial Goods sector index companies listed on the IDX during the 2017-2021 period. The number of samples used was 40 companies as research objects for five years. Panel data regression analysis was used as a mechanism in this study. The results showed that firm size significantly affects strong values with a negative coefficient direction. On the other hand, funding decisions and financial performance do not affect firm value. Therefore, it is concluded that fit size has a significant effect on solid buy with a negative coefficient direction, indicating that the larger the size of the company, the greater the agency costs that the company must incur to overcome agency problems and diversify into products that are less profitable and absorb a lot of resources, so this can reduce the value of the company.